PRÉ-TEXTUAIS - Ra'e Ga - O Espaço Geográfico em Análise, Revista; Silveira, Claudinei Taborda da; Silveira, Ricardo Michael Pinheiro; Neuman, Gisele (Ra'e Ga: o Espaço Geográfico em Análise, 2014)
Claudinei Taborda da Silveira, Ricardo Michael Pinheiro Silveira, Gisele Neuman